2004
DOI: 10.1080/13685530400004181
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sex hormone levels and some metabolic factors in men with coronary atherosclerosis

Abstract: Low levels of total testosterone, testosterone/estradiol ratio and free androgen index and higher levels of estrone in men with coronary artery disease appear together with many features of metabolic syndrome and may be involved in the pathogenesis of coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 34 publications
(28 reference statements)
4
29
0
Order By: Relevance
“…Excess glucocorticoids have also been shown to decrease the number of insulin receptors and affinity in rat liver and adipocytes (Kahn et al, 1978;Buren et al, 2002). Likewise, low levels of estradiol were shown to be associated with insulin resistance in men (Dunajska et al, 2004). In view of these findings, it is proposed that castration-induced changes in corticosterone and estradiol could have contributed for the changes recorded in the present study.…”
Section: Discussionsupporting
confidence: 41%
“…Excess glucocorticoids have also been shown to decrease the number of insulin receptors and affinity in rat liver and adipocytes (Kahn et al, 1978;Buren et al, 2002). Likewise, low levels of estradiol were shown to be associated with insulin resistance in men (Dunajska et al, 2004). In view of these findings, it is proposed that castration-induced changes in corticosterone and estradiol could have contributed for the changes recorded in the present study.…”
Section: Discussionsupporting
confidence: 41%
“…27 It has been reported that the lack of male sex hormone is an independent risk factor that contributes to hypercholesterolemia and hyperlipidemia and increases the risk for developing CHD. [28][29][30] Testosterone replacement therapy in hypogonadal men delays CVD by lowering total cholesterol. However, testosterone replacement therapy increases the incidence of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Men with low testosterone levels are often more obese, hypertensive, and have increased blood glucose and serum cholesterol levels and increased carotid artery atherosclerosis with diabetes (5, 7). Additionally, Dunajaska et al (6) have shown that low levels of total testosterone, testosterone/estradiol ratio, and free androgen index are associated with coronary artery disease in men. These findings underscore the need to fully understand the effects of testosterone on coronary vascular wall biology.…”
mentioning
confidence: 99%